Food allergy: Diagnosis, management & emerging therapies - Robison, Rachel Glick (Medknow Publications & Media Pvt Ltd, 2014)
IgE-mediated food allergy is an important health concern with increasing prevalence worldwide. Manifestations of IgE-mediated food allergy include urticaria, angioedema, pruritus, difficulty in breathing, laryngeal oedema, vomiting, diarrhoea and/or hypotension within minutes to two hours of the offending food's ingestion. Diagnosis requires both a careful history and supportive testing with laboratory studies and possibly oral food challenges. Current treatment of food allergy focuses on avoidance of the allergen and prompt emergency management of reactions. Epinephrine autoinjectors are provided to patients for the treatment of severe reactions. More research is needed to determine the optimal timing with which to introduce common allergens into a child's diet to possibly prevent the development of food allergy. Novel therapies are under investigation given the difficulty of allergen avoidance and the potentially fatal nature of reactions. Both allergen specific therapies such as oral, sublingual and epicutaneous immunotherapy and allergen non-specific therapies such the Chinese herbal formula FAHF-2 and omalizumab show promise though more data on efficacy and long-term safety are needed before these therapies become mainstream.